Implementation and Utilization of AI in Conceptualizing Educational Video Content on the Importance of Using Sunscreen in Daily Activities - Aulia, Ratih; Rambe, Aripin; Nuary Singarimbun, Roy (Journal of Technology and Computer, 2025)
This research explores the application of Artificial Intelligence (AI) in developing educational video concepts, specifically focusing on the daily importance of sunscreen use. Recognising AI's capacity to enhance human activities, this study leverages it as a tool for crafting engaging and informative video content. Sunscreen is vital for protecting skin from harmful ultraviolet radiation, necessitating effective public education—video being a key medium. Employing a qualitative, descriptive methodology, this study gathered data through observing and analysing educational videos on social media. The video concept creation primarily utilised ChatGPT, an AI platform, with final video production handled by InShot and CapCut. The findings reveal that AI significantly simplifies and accelerates the video concept generation process, drastically reducing production time. This also allows for the creation of a wide variety of video styles and themes, extending beyond just sunscreen education. The core benefits of integrating AI into this workflow include enhanced time efficiency, streamlined content creation, and remarkable flexibility in generating concepts tailored to specific educational goals. Ultimately, implementing AI in video production promises to empower both the public and content creators to disseminate information with greater effectiveness and creativity.